1990
DOI: 10.1128/iai.58.6.1992-1994.1990
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori urease activity is toxic to human gastric epithelial cells

Abstract: A human gastric adenocarcinoma cell line was used to evaluate the contribution of urease from Helicobacter (formerly Campylobacter) pylori to its cytotoxicity. Gastric cells cultured in medium supplemented with 20 mM urea were exposed to 5 x 10(6) CFU of H. pylori per ml with or without the addition of a urease inhibitor, acetohydroxamic acid. Viabilities of cells exposed to H. pylori for 2, 24, and 48 h, assessed by incorporation of neutral red dye, were 60, 27, and 16%, respectively; however, the viabilities… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
63
0
2

Year Published

1991
1991
2004
2004

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 193 publications
(66 citation statements)
references
References 8 publications
1
63
0
2
Order By: Relevance
“…In addition to its involvement in colonization, urease is also believed to mediate certain pathogenic processes. The activity of H. pyiori urease has been postulated to affect various aspects of gastric physiology including transepithelial H* ion flow (Hazell and Lee, 1986), the constituency of gastric mucus (Sidebotham and Baron, 1990) and the viability of gastric epitheiiai ceiis (Smoot et aL, 1990). it has been shown that H. pylori urease activity acting in concert with a cytotoxin causes vacuoiation in iHeLa tissue culture cells (Cover et aL, 1991).…”
mentioning
confidence: 99%
“…In addition to its involvement in colonization, urease is also believed to mediate certain pathogenic processes. The activity of H. pyiori urease has been postulated to affect various aspects of gastric physiology including transepithelial H* ion flow (Hazell and Lee, 1986), the constituency of gastric mucus (Sidebotham and Baron, 1990) and the viability of gastric epitheiiai ceiis (Smoot et aL, 1990). it has been shown that H. pylori urease activity acting in concert with a cytotoxin causes vacuoiation in iHeLa tissue culture cells (Cover et aL, 1991).…”
mentioning
confidence: 99%
“…Production of ammonium by urease could result in the back diffusion of hydrogen ions which may increase acidity at the gastric mucosal surface (Hazell and Lee, 1986) or may damage the integrity of the mucosa. It has also been shown that the presence of ammonium potentates cytotoxic effects of H. pylori on cultured human gastric epithelial cells (Smoot et al, 1990;Cover et al, 1991).…”
Section: Oral Diseasesmentioning
confidence: 99%
“…The ammonia released after the hydrolyzation of urea is likely to neutralize the hydrochloric acid. Ammonia may also be directly toxic to the gastric epithelial cells (Smoot et al 1990). Further cell damage may be caused by cytotoxins, one of which has been shown to lead to vacuolization in vitro (Leunk et a/.…”
Section: Pathogenetic Aspectsmentioning
confidence: 99%